Nurses’ attitudes toward professional attire: a cross-sectional study of preferences for scrubs versus white coats - Parvaneh Khorasani; Aylin Kamrani; Seyed Majid Khaze; Hossein Ghasemi (BMC Nursing)
Abstract Background Professional uniforms are a key component in conveying the identity, authority, and responsibilities of healthcare personnel. In Iran and several other Middle Eastern countries, the traditional white coat remains the standard nursing uniform. However, this practice often blurs the distinction between nurses and other members of the healthcare team, potentially leading to confusion and dissatisfaction among both patients and nursing staff. This study aimed to explore nurses’ attitudes toward their professional uniforms and to examine their preferences between scrubs and white coats. Methods This descriptive-analytical, survey-based study was conducted among 402 nurses employed in hospitals across Isfahan, Iran, selected using a convenience sampling method. Data were collected via a two-part questionnaire: the first part captured demographic data, while the second assessed perceptions related to nursing uniforms. Content validity was established through expert review, and internal consistency was confirmed using Cronbach’s alpha. Descriptive statistics and inferential analyses—including independent t-tests and Chi-square tests—were used to analyze the data. Results The average age of the participating nurses was 34.49 years. Most were female, married, and held a bachelor’s degree in nursing. Statistically significant associations were found between gender and educational level and various uniform-related factors, including appearance, comfort, sense of identity, and self-confidence (p < 0.05). Overall, nurses demonstrated a clear preference for scrubs over white coats, with navy blue and light blue identified as the most favored colors. Conclusion The findings indicate a strong preference among hospital nurses for standardized scrubs over traditional white coats across several key dimensions. Participants also emphasized the importance of using color differentiation for various departments and generally viewed white as an unsuitable universal uniform color. These insights can support nursing managers in developing evidence-based, standardized uniforms that align with clinical demands and staff preferences.